Melacak Gerakan Radikal Islam dari Wahabisme ke Global Salafisme - Rofhani Rofhani (Religió: Jurnal Studi Agama-agama, 2015)
The movement of Salafism constitutes part of the Islamic history of fundamentalism. They call their self as Salafis, who etymologically means “what had passed through and gone before” or “the outdistancing group”. The appearance of Global-Salafism apparently starts from the will of coming back to the past, which is the period of as-Salaf ash-S{âlih}. In the next development, it had to deal with the shifting perspective from theological nuance into political movement (Jihad-Salafism) which well issued by the appearance of phenomenon of many radical movements. Discourse about Salafism therefore is actually being pretentious after the tragedy of World Trade Center (WTC), September 11, 2001. Salafism is Islamic radical movement which attempts to modify Islamic traditional legacy. Unlike other group on Islamic movement that use religious reform within their progress, Salafism uses retrograde process as practical method. This article aims to explore at least three issues concerning with Salafism: (1) the basic doctrine of Salafism and its response to politics, (2) its movement and fragmentation, and (3) how it constructs follower’s conviction in different states in the world. This article primarily refers to Roel Meijer’s book, Global Salafism; Islam’s New Religious Movement. In this book, Meijer wrote about intellectual’s concern and care for global Salafism. In addition, this article also refers to other references to enrich its analysis, specifically the social influences of global Salafism.